Retroviral nucleic acid and method of use. - Allaudin, Zeenathul Nazariah; Mohd Lila, Mohd Azmi; Nik Abd Rahman, Nik Mohd Afizan (2009)

(untitled)
The present invention provides a retroviral nucleic acid capable of tissue-specific expression of a heterologous nucleic acid in cell and uses thereof. The present invention also provides a recombinant replication incompetent retrovirus and uses thereof.